Theory of iterations and monounary algebra in hight school - Helena Binterová, Pavel Tlustý (Littera Scripta, 2011)
In this article we were concentrated on the possibilities of iteration theory usage in the theory of monounary algebras. We studied especially two-parameter family of quadratic function f(x,t,s) = f(x+t)2 +s, among others because of the importance of quadratic functions in school mathematics and signiﬁcance of simple non-linear models. We were thinking about the description of blocks of conjugated functions.